A personality and impairment approach to examine the similarities and differences between avoidant personality disorder and social anxiety disorder. (22nd September 2016) - Carmichael, Kieran L. C.; Sellbom, Martin; Liggett, Jacqueline; Smith, Alexander
ABSTRACT: The current study examined whether avoidant personality disorder (AvPD) and social anxiety disorder (SAD) should be considered distinct disorder constructs, which is a persistent and controversial issue in the clinical literature. We examined whether relative scores on SAD and AvPD were associated with the same personality profile and severity of impairment. The current research used a cross‐sectional design and self‐report inventories, including multiple measures of personality, impairment and psychopathology. Results from a mixed sample of 402 university and community participants found that scores on AvPD and SAD were similarly associated with personality traits and impairment indices. Moreover, a latent construct accounting for the shared variance for AvPD and SAD was associated with personality traits and impairment, whereas the residuals representing the uniquenesses of these disorder constructs were not. These findings support the view that AvPD and SAD are similar disorders from a phenotypic personality trait and impairment perspective. These findings are contrary to a prevalent view in the literature, known as severity continuum hypothesis, because the two disorders could not be meaningfully differentiated based on severity of impairment. Copyright © 2016 John Wiley & Sons, Ltd.